The Influence of Palm Oil Empty Fruit Bunches (TKKS) and NPK Addition on The Growth of Robusta Coffee Seedlings (Coffea canephora L.) - Eva Rosdiana; Amanda, Zenitasari; Setyoko, Ujang; Fandyka Yufriza Ali (Jurnal Riset Perkebunan, 2025)
Coffee is one of Indonesia's prominent tree commodity plants. In both generative and vegetative propagation, one crucial consideration is the choice of growing media rich in macro and micro nutrients. This study aims to investigate the effect of different ratios of palm oil empty fruit bunch (TKKS) and the addition of NPK fertilizer on the growth of robusta coffee seedlings. The research was conducted from January to May 2024 at the Innovation Garden, State Polytechnic of Jember. This study employed a factorial Randomized Complete Block Design (RCBD) with 2 factors, each having 3 treatment levels. The first factor was the growing media ratio: T1 = Top Soil : TKKS : Sand (1:1:1), T2 = Top Soil : TKKS : Sand (2:1:1), T3 = Top Soil : TKKS : Sand (1:2:1). The second factor was NPK fertilizer application: N1 (1 gram NPK/polybag), N2 (1.5 grams NPK/polybag), N3 (2 grams NPK/polybag). These combinations resulted in 9 treatment groups, each replicated 3 times, totaling 27 experimental units. Data were analyzed using ANOVA, followed by Tukey’s HSD test at a 5% significance level (p < 0.05), using SPSS version 25. The results showed that the T3 growing media (1:2:1) significantly increased seedling height by 18.7%, stem diameter by 15.2%, leaf number by 17.4%, and root length by 22.5% compared to T1 (p < 0.05). Application of 1.5 g NPK/polybag (N2) increased seedling height by 12.3% (p < 0.05) and root length by 19.8% (p < 0.01) compared to N1. A significant interaction (p < 0.05) was observed between T3 media and 1.5 g NPK/polybag, specifically enhancing root length, indicating a synergistic effect on root development.